Imperial College London Business School Distance-Learning MBA Programme: Lifelong Education for Physicians using e-Learning - SEKINE, Michikazu (Igaku Kyoiku / Medical Education (Japan), 2010)
1) As medicine matures, a more balanced management of human resources, medical skills and technology, and finance is required. Therefore, the importance of business administration as a subject of lifelong learning by physicians is increasing. 2) Japanese medical students and physicians have few opportunities to learn business administration. A distance-learning programme for a masters of business administration (MBA) degree provides a learning opportunity that does not interrupt careers. 3) For both providers and learners, much effort is needed to avoid leaving school without completing the MBA course: while learners need more time management and motivation, providers need to develop a better management system and provide virtual reality situations.